Secretory leukocyte protease inhibitor and its role in virus induced head and neck cancers - Ajila Vidya; Shetty Veena; Subhas Babu G.; Hegde Shruthi (Medicinski fakultet i Klinika za stomatologiju, Niš, 2019)
Introduction: Oral squamous cell carcinoma (OSCC) is the commonest oral malignancy and accounts for over 90% of oral cancers. Though tobacco consumption in its various forms is the main etiological agent, nowadays, the incidence of virus induced cancers is increasing. Human Secretory Leukocyte Protease Inhibitor (SLPI) is a member of the innate immunity-associated proteins. It has a variety of actions including anti-inflammatory, antibacterial antifungal and antiviral effects. SLPI has been identified as the single most potent factor in preventing the transmission of HIV-1 through oral secretions. Studies have recently demonstrated an effect against virus induced oral cancers. The most commonly studied viruses in oral oncogenesis include Human Papilloma Virus, Epstein Barr Virus and Herpes simplex virus. SLPI has shown an inverse correlation with the occurrence of HPV-positive tumours. In the presence of HSV infection, there is a down regulation of SLPI. Decreased SLPI has been noted in Epstein Barr Virus associated nasopharyngeal carcinoma. The present review discusses the diverse effects of SLPI with special focus on its effects on Human Immunodeficiency Virus, Human Papilloma Virus, Herpes Simplex Virus and Epstein Barr Virus. Conclusion: Increased SLPI has a protective role in viral oncogenesis while decreased levels increase the probability of viral infection.